Prevalence of Urinary Incontinence in Pregnant Women at Tertiary Care Hospitals in KhonKaen Province - Wanee Tingthong; Pranom Buppasiri Buppasiri; Chompilas Chongsomchai; Teerayut Temtanakitpaisan; Ussanee Sangkomkamhang (The Royal Thai College of Obstetricians and Gynaecologists, 2014)
Objective:To determine prevalence of urinary incontinence during pregnancy.Material and Method: A descriptive, cross sectional study was conducted. Total of 330 pregnant women, aged 15 to 43 years, attended antenatal care clinic at two tertiary care hospitals (Srinagarind and KhonKaen) in KhonKaen province between March and July 2013 were recruited. Self-administered questionnaires which was modified from International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) were used to collect baseline data and urinary symptoms.Results:There were 330 pregnant women participation in this study. The prevalence of urinary incontinence during pregnancy was 59 in 330 (17.9%, 95% CI = 13.9-22.4). Of this, forty (67.8%) pregnant women suffered from stress urinary incontinence, 27.1% from urge urinary incontinence. The risk factors for urinary incontinence on univariable analysis were multiparous (p = 0.004), age > 35 years (p = 0.035), caffeine intake (p = 0.001). But on multivariable analysis, the risk factors for urinary incontinence during pregnancy were multiparous (OR=2.3, 95%CI 1.3-4.1) and caffeine intake (OR 3.1, 95%CI 1.6-6.1)Conclusions: The prevalence of urinary incontinence during pregnancy was high. Multiparity and caffeine intake contributed major risk factors.